Molecular Analysis of Vancomycin-Resistant Enterococci Isolated from Regional Hospitals in Trinidad and Tobago - Akpaka, Patrick E. (Adv Med, 2016)
Geographic spread of vancomycin-resistant enterococci (VRE) clones in cities, countries, or even continents has been identified by molecular techniques. This study aimed at characterizing virulent genes and determining genetic relatedness of 45 VRE isolates from Trinidad and Tobago using molecular tools, including polymerase chain reaction, pulsed-field gel electrophoresis (PFGE), and Random Amplification Polymorphic DNA (RAPD). The majority (84%) of the isolates were Enterococcus faecium possessing vanA gene while the rest (16%) were Enterococcus faecalis possessing vanB. The esp gene was found in all 45 VRE isolates while hyl genes were found only in E. faecium species. The E. faecium species expressed five distinct PFGE patterns. The predominant clones with similar or common patterns belonged to clones one and three, and each had 11 (29%) of the VRE isolates. Plasmid content was identified in representative isolates from each clonal group. By contrast, the E. faecalis species had one PFGE pattern suggesting the presence of an occult and limited clonal spread. The emergence of VRE in the country seems to be related to intra/interhospital dissemination of an epidemic clone carrying the vanA element. Therefore, infection control measures will be warranted to prevent any potential outbreak and spread of VRE in the country.